2016
DOI: 10.1148/radiol.2015150892
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Features of Liver Lesions, Lung Nodules, and Renal Stones at Multi–Detector Row CT Examinations: Dependency on Radiation Dose and Reconstruction Algorithm

Abstract: Radiation dose settings and reconstruction algorithms affect the extraction and analysis of quantitative imaging features in lesions at multi-detector row CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 19 publications
(22 reference statements)
4
86
2
Order By: Relevance
“…In contrast, the segmentation-based parameters depend not only on the stone but also on the delineation between the urinary stone and the background, which can be achieved differently with or without human interaction [2125]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the segmentation-based parameters depend not only on the stone but also on the delineation between the urinary stone and the background, which can be achieved differently with or without human interaction [2125]. …”
Section: Discussionmentioning
confidence: 99%
“…Further, only images reconstructed with traditional filtered back projection were considered. Iterative reconstruction (IR) algorithms are increasingly being used in practice and are known to produce images with differing textures 19,34 . However, due to the proprietary nature and continuous evolution of these IR algorithms, developing a consistent set of radiomics features that accurately describe the tumor microenvironments, or developing correction factors from images reconstructed using IR may not be practically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients with lung adenocarcinoma, Coroller, et al 6 reported 35 radiomic features to be prognostic for distant metastasis and 12 features that predict survival. However, any value and practicality of noninvasively quantifying tumor characteristics is largely dependent on the repeatability and reproducibility of quantitative imaging features across medical imaging devices 619, 32 . As such, prior to the clinical application of radiomic features for patient care, they must be found to be repeatable and reproducible under the conditions that might be expected in clinical practice or a clinical trial with multiple scanners or sites 619, 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the same study referenced above that compared features computed from multiple segmentations also indicated that implementations from separate institutions of purportedly the same feature sometimes produced different values. 61,68 Thus, a predictive model built for lung nodule characterization may be validated in one cohort and fail in another because of differences in the data acquisition and reconstruction. [11][12][13] In addition to the challenges raised by segmentation, a final challenge is the sensitivity of radiomics features to image acquisition and reconstruction (ie, the heterogeneity of image acquisitions).…”
Section: Challenges To Conventional Radiomicsmentioning
confidence: 99%